2012
DOI: 10.1371/journal.pone.0031439
|View full text |Cite
|
Sign up to set email alerts
|

No Differential Regulation of Dopamine Transporter (DAT) and Vesicular Monoamine Transporter 2 (VMAT2) Binding in a Primate Model of Parkinson Disease

Abstract: Radioligands for DAT and VMAT2 are widely used presynaptic markers for assessing dopamine (DA) nerve terminals in Parkinson disease (PD). Previous in vivo imaging and postmortem studies suggest that these transporter sites may be regulated as the numbers of nigrostriatal neurons change in pathologic conditions. To investigate this issue, we used in vitro quantitative autoradioradiography to measure striatal DAT and VMAT2 specific binding in postmortem brain from 14 monkeys after unilateral internal carotid art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 30 publications
(55 citation statements)
references
References 49 publications
3
52
0
Order By: Relevance
“…9), and all striatal measures correlated strongly with each other; but note that these postmortem measures were done only 2 months after MPTP. 9,29 The consistency of all of the terminal field measures strongly supports that the relationship between terminal fields and nigral cell bodies does not reflect insensitivity of the striatal measures.…”
Section: Measurement Of Pd Severitymentioning
confidence: 63%
“…9), and all striatal measures correlated strongly with each other; but note that these postmortem measures were done only 2 months after MPTP. 9,29 The consistency of all of the terminal field measures strongly supports that the relationship between terminal fields and nigral cell bodies does not reflect insensitivity of the striatal measures.…”
Section: Measurement Of Pd Severitymentioning
confidence: 63%
“…All 16 monkeys completed the study and demonstrated a wide range of severity of parkinsonism from none in controls to severe unilateral parkinsonism with the highest doses of MPTP (Tabbal et al, 2012). All routine animal care procedures were described in detail (Tian et al, 2012). …”
Section: Methodsmentioning
confidence: 99%
“…Detailed descriptions of the approaches have been published earlier (Brown et al, 2012; Karimi et al, 2013; Tabbal et al, 2012; Tian et al, 2012). The following is a short overview.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Striatal dopamine was measured in the tissue extracts using high performance liquid chromatography with electrochemical detection (HPLC-EC) (Karimi et al, 2006; Tian et al, 2012). The analytical data were expressed as ng/g of brain tissue.…”
Section: Methodsmentioning
confidence: 99%